Um estudo preliminar sobre a prosódia de construções com tópico e foco no português paulista - Yano, Cynthia Tomoe (2020)
This paper aims at analyzing prosodic strategies related to the prosodic phrasing and the tonal configuration associated with topic and focus constructions in declarative sentences of Brazilian Portuguese (BP), focusing on the dialect spoken in the city of São Paulo, not yet described in that sense. From the analysis of data produced by speakers from São Paulo, it was noted that the strategies employed to mark focus and topic are similar to the ones described in previous studies for other dialects of BP (MORAES; ORSINI, 2003; ORSINI, 2005; FERNANDES, 2007; TRUCKENBRODT et al., 2009; FROTA et al., 2015; among others). That is, there seems to be a distinction between the two types of construction, since topics, regardless of their position in the sentence, tend to form independent intonational phrases (I), presenting a pause and a low or high boundary tone at its right border. However, focused expressions do not necessarily form an independent I, since, in initial position, a low phrasal accent may be associated with the right edge of the phonological phrase (φ) that contains the focused expression, and therefore, this domain is contained in the same I that includes the rest of the sentence.